Magical Realism in the Contemporary Arabic Novel: The Forbidden Paradise by Yahya Al-Qaisi as a Model - Aldiabat, Ali Mohammad; Boras, Wafa (Journal of Ecohumanism, 2024)
Literary creativity depends heavily on imagination during the process of artistic creation, but its presence differs from one literary work to another. The need for literary creativity has increased, especially with the advent of the modern era and coinciding with the social and political changes that have occurred at various levels. This made the creator move from reality to transcend it to other worlds that are closer to magic. This is what we observed in many literary genres, the most important of which is the novel. Therefore, we chose the novel The Forbidden Paradise by Yahya Al-Qaisi because of its departure from the usual language, on the one hand, as its language was intensely poetic, in which the Sufi (mystic) language, with its dimensions and connotations, open the door for endless interpretations, as well as its consideration of some realistic phenomena, on the other hand, such as the search for treasures and troves and the fantastic and peculiar secrets that occur during these attempts that enter into the world of magic and prediction of the future, with all the connotations of the third eye of insight and foresight. With this he could mix modernity through the messages that he receives via e-mail from figures aware of the ignorance that he embodies in their way of thinking, which does not go beyond primitive mentality, violating all physical sciences and even geology. This is natural because magic requires revolution against everything that is realistic and physical in order to transcend it to everything that is unreal and metaphysical